Tipologi Atap Rumah Tinggal Di Pemukiman Kauman Malang - Hartati Kapita; Lintang Satiti Mahabella (Peneliti.net, 2020)
The roof of typology of residential house in a poor kauman settlement described and characterized its owner, a part of construction which appeared character and it was covered by human being was construction facade. Facade was a part of first building covered of the eye and described as style and architecture, facade can contribute description about building functions. Beside that, facade was functioned as recorder of human civilization history. This research talked about typology facade of construction which one is roof typology of residential house in a poor kauman settlement. Result of the research stated that there were 8 types of residential roof house, they are: roof shield doubles, roof shield pyramid, shield compound, saddle, roof gevel saddle split, gevel, listplank